al-Furȗq fî al-Mȗrfîmât bayn al-‘Arabiyyah wa al-Injilîziyyah “al-Mȗrfîm (Mâ) al-‘Arabiy wa al-Injilîziy (what) Anmȗdhajan - Lubna Farah Khan; Nuril Mufidah (Uktub: Journal of Arabic Studies, 2021)
This paper investigates Arabic and English morphemes with to identifying the similarities and differences between them. The differences between the two languages might be the main reason for making errors by Arab learners. It might help both teachers and learners to overcome these problems. By identifying the morphological differences between the two languages, teachers will determine how and what to teach, on the one hand, and students will know how and what to focus on when learning the target language, on the other. The Paper will shed light on phonological terms such as: "phonem, allophones, intonation, and accentuation" and their equivalents in English in order to identify the appropriate or opposing signs that affect the specificity of the sounds. We have followed the descriptive and analysis research methods. The results of study on morphemes have an interrogative and exclamatory function, and we find that the morpheme “what” is distinguished from the morpheme “ما”, which has other uses such as negation, infinitive, extra and accentuation.